The Meanings of Food Consumption, Consumer Effects and the Role of "Origin": The Case of Ethnic Food in Cameroon. Issue 4 (2nd October 2018) - Mefoute Badiang, Alphonse
ABSTRACT: This study examines the role of an individual's belonging to some ethnic groups as it relates to the meanings associated with food consumption as well as the outcome(s) of ethnic food consumption. To achieve this goal, data were collected from 607 individuals, using a survey and structural equations analysis. Findings revealed that ethnic food consumption triggers specific emotions associated with different ethnic origins; there is a significant and positive moderating effect of sense of belonging to the product's region of origin. Attachment serves as a mediator of the effect of ethnicity on commitment. These findings have several notable implications.